Cognitive education and its relationship with the performance of some discovery skills in students of the Faculty of Physical Education and Sports Sciences at Sulaimani University - Sulaiman, Asst. Prof. Dr. Hiwa Mohammed Ali; Abdullah, Asst. L. Razhan Hassan; Kaka, Asst. L. Sheheryar Faisal (Sulaimani Journal for Humanities, 2026)
The research aims to introduce the level of some of the discovery skills of students of the Faculty of Physical Education and Sports Sciences at Sulaimani University, and introduce the type of relationship between Cognitive acquisition and some discovery skills in students of the Faculty of Physical Education and Sports Sciences at Sulaimani University Due to the nature of the research problem, I chose to look at the research in a random way on third year students in the faculty of physical education and sports sciences There are (30) students in Sulaimani University for the academic season 2022 - According to the results of the study, there is a positive relationship between the level of cognitive learning and cognitive skills of students Faculty of Physical Education and Sports Sciences, which focuses on students with higher cognitive education possessing superior discovery skills. . . . . It is necessary to strengthen the cognitive aspect associated with discovery skills in the curriculum through theoretical content development to be appropriate with practical application.